Different Cropping Systems for Soil and Water Conservation-Conservation cropping Systems - Prasad, R.; bhan, Suraj (Journal of Soil and Water Conservation, 2022)
The conservation of soil and water resources is essential to sound agriculture and continued prosperity of the society. Soil conservation may be interpreted as prevention of erosion, preservation of good soil structure, maintenance of .organic matter and fertility. Water conservation is as important in dry part of the country as much rainfalls in that area should soak into ground and conserved in the soil for longer period to the future demand of the crop. Conservation cropping system is one of the most logical means of soil and water conservation, both in humid and dry-land agriculture. It may be defined as a "way of preventing various processes of soil loss by putting or slotting it to such use under which it will deteriorate least and produce most."